Physiotherapy management of patients with Peripheral Artery Disease in the Western Cape - Abrahams, Lisa (Division of Physiotherapy, 2024)
Peripheral artery disease is a growing public health burden of disability and death worldwide. This is especially the case in lower-income countries like South Africa. Peripheral artery disease is a risk factor for major cardiovascular events and a leading cause of non-traumatic lower limb amputations. In other countries, supervised exercise therapy has been proven to improve patient outcomes of pain and mobility. Community walking and treadmill walking to the point of claudication onset are established and effective forms of management for peripheral artery disease. These are challenged in an African context due to lack of resources or safety in the community. Minimal research has been done regarding conservative rehabilitation for people with peripheral artery disease in under-resourced environments. There is no known data about the physiotherapy management of people with peripheral artery disease in the Western Cape, South Africa. With ageing populations and risk factors such as obesity, sedentary lifestyle and diabetes mellitus expected to increase, it is of vital importance that we understand how this disabling condition is currently being managed in the Western Cape.